Mode-matching Generalised Scattering Matrix Based Electromagnetics Performance Analysis of Thick Frequency Selective Surfaces for Airborne Applications - Narayan, Shiv; Nair, Raveendranath U.; Jha, R. M. (Defence Science Journal, 2013)
Electromagnetic (EM) performance of thick aperture type FSS has been analyzed using mode-matching generalized scattering matrix (MM-GSM) technique for airborne radome applications. The MM-GSM technique facilitates accurate EM performance predictions for both single and multi-layered frequency selective surfaces (FSS) structures as it includes evanescent and propagating modes in the EM analysis. The computed transmission efficiency of the thick FSS structure over X-band at normal and near normal incidence shows excellent matching with the reported results in open domain. he study has been extended to determine the FSS band-pass transmission characteristics for incidence angles as high as 80° encountered in highly-streamlined nosecone radomes. Further, the dependence of transmission efficiency of the FSS structure on the dielectric parameters of the material filled within the apertures has also been analyzed. The present work shows that the proposed thick aperture-type FSS structure has potential applications in the design of airborne radomes. Defence Science Journal, 2013, 63(3), pp.249-253, DOI:http://dx.doi.org/10.14429/dsj.63.2426